Historia de Mayta: the committed narrator - Del Castillo Saldaña, Luis Ángel (2020)
Through his earliest novels, from a socialist perspective Vargas Llosa addressed the power of literature to contribute to social change, but with the novel Historia de Mayta he no longer espouses the collectivist ideal of yesteryear, the gradual or indirect changing of people’s lives towards a more just and equitable existence. Instead, his approach is more individualistic. The narrator-researcher of the novel represents an explicit and highly-colored reflection upon the ideological change undergone by Vargas Llosa, upon his work as a novelist, and upon his new approach to literature, in accordance with his new liberal position.